THE EFFECTIVENESS OF GOVERNMENT INSTAGRAM ACCOUNT TO FULFILL THE INFORMATION NEEDS STUDY ON @HUMASKOTATANGSEL - Fahmil Hakim; Karina Jayanti (Journal of Digital Media Communication, 2022)
South Tangerang City has official government social media accounts as their information media through the Communication and Informatics Service work unit @humaskotatangsel. This account is a medium that provides information to the public. The purpose of this study was to see the effectiveness of the @humaskotatangsel Instagram account in meeting the information needs of its people. This research uses quantitative research methods and the positivism paradigm. The data collection technique was carried out using a survey method using a questionnaire with a quota sampling technique. The respondents in this study were followers of the Instagram account @humaskotatangsel, which was calculated using the Slovin formula so that the total sample was 100 respondents. This study uses the uses and gratification theory, which assumes that media users play an active role in choosing and using which media is appropriate to meet their needs. In this case, the information needs of 48.3% of the fulfillment of the information needs of the people of Tangerang. And it is known from the results of the T-test that the value of t count (9.563) > t table (1.660). This figure shows Ho is rejected and Ha is accepted, which means there is an influence on the effectiveness of the @humaskotatangsel Instagram account in meeting the information needs of the Tangerang people.